2005
DOI: 10.1080/17453670510041781
|View full text |Cite
|
Sign up to set email alerts
|

Trochleaplasty for patellar instability due to trochlear dysplasia

Abstract: Patellofemoral instability with underlying trochlear dysplasia can be treated successfully by trochleaplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(120 citation statements)
references
References 12 publications
9
110
0
1
Order By: Relevance
“…This leads to an increased risk of patellofemoral tracking disorder, instability, dislocation, and ultimately cartilage injury [27]. One study found an association between increased sulcus angle and increased medial and lateral cartilage injury in patients with osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to an increased risk of patellofemoral tracking disorder, instability, dislocation, and ultimately cartilage injury [27]. One study found an association between increased sulcus angle and increased medial and lateral cartilage injury in patients with osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, no redislocation or subluxation occurred [5,32], but exact evaluation of the morphological changes after trochleoplasty is missing. Until today radiographic outcome after trochleoplasty was determined on plain radiographs only [32,39].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical examination, the patients presented a positive apprehension sign [32]. All patients had radiological signs of trochlear dysplasia (positive crossing sign, decreased trochlear depth, positive translation) [11].…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations